Acute effects of Maitland’s central posteroanterior mobilization on youth with low back pain. - Abe, Karina Yuko; Tozim, Beatriz Mendes; Navega, Marcelo Tavella (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Introduction: The low back pain is the most prevalent between the musculoskeletal disorders, and it is the most common reasons of absence from work. The flexibility, mobility, strength and endurance of the low back stability influence and the disharmony between these factors may result in low back pain. One of Maitland’s technique, which alter these factors, is posteroanterior (PA) mobilization. Objective: To analyze the posterior chain’s flexibility, low back’s mobility, trunk extensor’s endurance and low back extensors’ muscle strength after performed one treatment session using the Maitland method on youth with low back pain. Method: For this research, sixteen women (22 ± 3.03 years) with chronic low back pain participated. All volunteers were evaluated according to their perception of pain, flexibility, mobility, muscular strength and muscular endurance. The treatment protocol was the application of PA mobilization on the five lumbar vertebrae, from caudal direction to cranial, of three series of one minute in each vertebra. The same procedures of the initial evaluation were performed after the immediate application of PA mobilization technique (revaluation 1) and 7 days after the protocol (revaluation 2). The data were analyzed by the Shapiro-Wilk’s normality test; analysis of variance (ANOVA) repeated measures one-way with pos-hoc Bonferroni and Friedman’s ANOVA with pos-hoc Wilcoxon, with the level of significance of 5% (p< 0,05). Results: After PA mobilization application, there were significant improvements in muscular strength (immediate post-treatment and past seven days) and muscular endurance (immediate post-treatment). There were no significant improvements in the other variables, such as, level of pain, and lumbar flexibility and mobility. Conclusion: The lumbar PA mobilization was effective for increasing muscular strength and endurance, with stabilization of the level of pain, flexibility and mobility.